2022
DOI: 10.3389/fmicb.2022.824052
|View full text |Cite
|
Sign up to set email alerts
|

High Affinity Iron Acquisition Systems Facilitate but Are Not Essential for Colonization of Chickens by Salmonella Enteritidis

Abstract: The roles of TonB mediated Fe3+ (ferric iron) uptake via enterobactin (involving biosynthesis genes entABCDEF) and Fe2+ (ferrous iron) uptake through the FeoABC transporter are poorly defined in the context of chicken-Salmonella interactions. Both uptake systems are believed to be the major contributors of iron supply in the Salmonella life cycle. Current evidence suggests that these iron uptake systems play a major role in pathogenesis in mammals and as such, they represent promising antibacterial targets wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Our previous report showed that “active” colonization of the cecum with SEn strain LS101 occurred between 24 and 48 h p.i. in day-old birds challenged with the 10 9 CFU dose ( 21 ). In that study, the cecal Salmonella burden reached a maximum of ~10 9 CFU/g 24 and 48 h p.i.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous report showed that “active” colonization of the cecum with SEn strain LS101 occurred between 24 and 48 h p.i. in day-old birds challenged with the 10 9 CFU dose ( 21 ). In that study, the cecal Salmonella burden reached a maximum of ~10 9 CFU/g 24 and 48 h p.i.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, an experiment from our previous study provided evidence that yolk sac infection was not visualized prior to day 2 p.i. by LS101 sig70c35 [Supplementary Figure 4 of ( 21 )]. The passage of the yolk stalk gets partially occluded by lymphocyte proliferation minimizing the transfer of material between the yolk and the jejunum ( 25 ).…”
Section: Discussionmentioning
confidence: 99%